PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBANGUN SIKAP MODERASI BERAGMA PADA PESERTA DIDIK DI SMP NEGERI 10 BUTON TENGAH - Dian, Dianfitri; Darmayanti; Ridwan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the role of Islamic Religious Education (PAI) teachers in fostering religious moderation attitudes among students and to describe the manifestation of religious moderation attitudes that have developed at SMP Negeri 10 Buton Tengah. This research employed a qualitative approach using a case study design. Data were collected through participatory observation, in-depth interviews, and documentation, and subsequently analyzed using the interactive analysis model of Miles, Huberman, and Saldaña, encompassing data condensation, data display, and conclusion drawing. Data validity was ensured through source triangulation and technique triangulation. The findings reveal that PAI teachers effectively carried out multidimensional roles, encompassing the role of contextual educator, moderate role model, inclusive learning facilitator, and digital religious literacy guide. These roles operated synergistically and produced tangible impacts on students' character development. Students' religious moderation attitudes were well established, as reflected in active tolerance, organic harmony, openness to differences, and resilience against extremist influences in the digital era. These findings affirm that moderately oriented religious education possesses strong transformative power in shaping a generation of young people who are tolerant, peaceful, and of good character, while also contributing to the achievement of the Sustainable Development Goals, particularly in the domains of quality education and sustainable peace.